Methotrexate coated tablet and preparation method thereof
By optimizing the formula and preparation process of methotrexate coated tablets, combined with specific ingredients and steps, the problem of unstable tablet quality is solved, and the stable release of drugs is achieved and the therapeutic effect is improved.
Patent Information
- Application Number
- CN202411677749.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-01-03
AI Technical Summary
In the prior art, the formula and preparation process of methotrexate coated tablets are not optimized enough, and it is impossible to effectively take into account the synergistic effects of each component of the tablet core and the performance of the coating layer, resulting in unstable tablet quality and affecting the therapeutic effect of the drug.
Using specific ratios of methotrexate, microcrystalline cellulose, lactose, cross-linked povidone, sodium carboxymethyl starch, hydroxypropyl methyl cellulose and magnesium stearate, through grinding, drying and mixing , granulation, tableting and coating, etc., to prepare methotrexate coated tablets with stable disintegration properties and suitable particle size.
It ensures the effective content and appropriate particle size of methotrexate, improves the disintegration performance and hardness of the tablet, stabilizes the release and absorption of the drug, and improves the therapeutic effect of the drug.
Smart Images

Figure CN119235808A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of pharmaceutical preparations, and more specifically, to a methotrexate coated tablet and a preparation method thereof. Background Art
[0002] Methotrexate is a commonly used drug with important applications in the medical field. The research on pharmaceutical preparations in the prior art continues to develop, including the preparation of tablets. In the preparation of tablets, it is necessary to consider the content of the active ingredient of the drug, the particle size, and the selection and proportion of auxiliary materials such as fillers, disintegrants, binders, lubricants, etc., and also pay attention to the materials and properties of the coating layer. Different ingredients and processes will affect the quality of tablets, such as disintegration performance, hardness, weight difference, and drug release and absorption.
[0003] In the process of implementing the embodiments of the present invention, the inventors found that there are at least the following problems or defects in the prior art: the formula and preparation process of methotrexate coated tablets may not be optimized enough, and it is impossible to take into account the synergistic effect of the components of the tablet core and the performance of the coating layer, resulting in unstable tablet quality and affecting the therapeutic effect of the drug. Summary of the invention
[0004] The invention provides a methotrexate coated tablet and a preparation method thereof.
[0005] In a first aspect of the present invention, there is provided a methotrexate coated tablet comprising:
[0006] The tablet core and the coating layer, the tablet core contains methotrexate, a filler, a disintegrant, a binder and a lubricant, the weight proportion of methotrexate in the tablet core is 5%-15%, the purity is not less than 98%, and the particle size range is 10-50 microns.
[0007] Furthermore, the filler is microcrystalline cellulose, lactose or a mixture of the two, accounting for 40%-70% by weight in the tablet core, the particle size of the microcrystalline cellulose is 50-200 microns, the lactose is of pharmaceutical grade, and the moisture content does not exceed 0.5%.
[0008] Furthermore, the disintegrants are cross-linked polyvinylpyrrolidone and sodium carboxymethyl starch, accounting for 5%-15% by weight in the tablet core, the cross-linked polyvinylpyrrolidone model is XL-10, and the degree of substitution of sodium carboxymethyl starch is 0.2-0.7.
[0009] Furthermore, the binder is hydroxypropyl methylcellulose and polyvinyl pyrrolidone, and its weight proportion in the tablet core is 3%-10%. The viscosity of hydroxypropyl methylcellulose is 3-6 mPa·s, and the K value of polyvinyl pyrrolidone is 25-35.
[0010] Furthermore, the lubricant is magnesium stearate, which accounts for 0.5%-2% by weight in the tablet core, and the particle size of the magnesium stearate is 1-10 microns.
[0011] Furthermore, the coating layer material is a gastric soluble film coating material, the weight of which accounts for 3%-8% of the weight of the tablet core, and the dissolution time of the material in a hydrochloric acid solution with a pH value of 1.2-3.0 does not exceed 30 minutes.
[0012] Furthermore, the gastric soluble film coating material comprises hydroxypropyl methylcellulose and polyethylene glycol, wherein the hydroxypropyl methylcellulose accounts for 60%-80% of the total weight of the coating material, and the molecular weight of the polyethylene glycol is 4000-6000.
[0013] In a second aspect of the present invention, there is provided a method for preparing a methotrexate coated tablet, comprising the following steps:
[0014] Tablet core material preparation: weigh the specified amount of methotrexate, filler, disintegrant, binder and lubricant; grind the methotrexate to a particle size of 10-30 microns; pass the filler in the form of microcrystalline cellulose through an 80-100 mesh sieve, and pass the lactose filler through a 100-120 mesh sieve; vacuum dry the disintegrant in the form of cross-linked polyvinylpyrrolidone and sodium carboxymethyl starch at 50-60°C for 2-3 hours, dry the binder in the form of hydroxypropyl methylcellulose and polyvinylpyrrolidone at 40-50°C for 3-4 hours, and dry the lubricant of magnesium stearate at 60-70°C for 1-2 hours;
[0015] Initial mixing: Place the treated methotrexate and half of the filler in a V-type mixer and mix at a speed of 10-15 rpm for 15-20 minutes. Then add the disintegrant and continue mixing at a speed of 12-18 rpm for 20-25 minutes;
[0016] Preparation of soft material: prepare the binder into a 5%-8% aqueous solution, slowly add it to the above mixture, and stir at a speed of 20-30 rpm until a soft material with a certain plasticity is formed. The humidity of the soft material is controlled at 20%-30%;
[0017] Granulation and drying: Use an oscillating granulator to make wet granules from the soft material through a 14-18 mesh screen. Spread the wet granules evenly on a tray with a thickness not exceeding 2 cm, place in a hot air circulation oven, and dry at 55-65°C for 3-4 hours, turning every 30 minutes, until the moisture content of the granules is less than 2%;
[0018] Granulation and total mixing: Use a 16-20 mesh screen to granulate the dried granules to remove fine powder and lumps. Place the granules after granulation together with the remaining fillers and lubricants in a three-dimensional motion mixer and mix at a speed of 10-15 rpm for 10-15 minutes;
[0019] Tablet pressing: Use a rotary tablet press for tablet pressing, with a tablet pressing pressure of 8-12kN, control the tablet weight difference within ±3%, and the tablet hardness of 5-7kg / cm 2 , thickness is 3-5 mm;
[0020] Preparation of coating solution: For the coating layer, hydroxypropyl methylcellulose and polyethylene glycol are mixed in proportion; wherein, hydroxypropyl methylcellulose is first swelled in hot water at 80-90°C and stirred until completely dissolved, and polyethylene glycol is heated to 60-70°C and melted and then added to prepare a coating solution with a solid content of 12%-18%;
[0021] Coating: Place the tablet core in a high-efficiency coating machine, set the inlet air temperature to 70-80℃, the outlet air temperature to 45-55℃, the coating machine speed to 6-8 rpm, and the spray speed to 6-8ml / min, and perform the coating operation until the tablet core weight gain reaches the specified value, and the coating is uniform and complete without cracking, shelling, etc.
[0022] Furthermore, in the initial mixing step, the relative humidity inside the V-type mixer should be controlled at 30%-40%, and the mixing uniformity of the materials should be checked every 5 minutes during the mixing process. The methotrexate content is detected by sampling to ensure that the methotrexate content deviation in each part of the material is within ±2%.
[0023] Furthermore, in the coating step, the spray gun pressure of the high-efficiency coating machine is controlled at 0.2-0.4MPa, and the coated tablets are sampled every 15-20 minutes during the coating process to observe the appearance and thickness of the coating, and the weight gain of the coating is tested by the weight method. The spray speed and the speed of the coating machine are adjusted in time according to the test results to ensure the stability of the coating quality.
[0024] The above-mentioned embodiments of the present invention have at least the following beneficial effects: the formula of the methotrexate coated tablets of the present invention can ensure the effective content and appropriate particle size of methotrexate, and the reasonable selection and ratio of fillers, disintegrants, binders and lubricants can ensure that the disintegration performance, hardness, weight difference, etc. of the tablets meet the requirements.
[0025] The selection of coating layer materials and the preparation process can make the coating dissolve under appropriate conditions, which is beneficial to the release and absorption of the drug. At the same time, the entire preparation method can ensure the stability of tablet quality and improve the therapeutic effect of the drug. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The above and other objects, features and advantages of the exemplary embodiments of the present invention will become readily understood by reading the detailed description below with reference to the accompanying drawings. In the accompanying drawings, several embodiments of the present invention are shown in an exemplary and non-limiting manner, in which:
[0027] Figure 1 A schematic flow chart of a method for preparing a methotrexate coated tablet provided in one embodiment of the present invention. DETAILED DESCRIPTION
[0028] The principles and spirit of the present invention will be described below with reference to several exemplary embodiments. It should be understood that these embodiments are provided only to enable those skilled in the art to better understand and implement the present invention, and are not intended to limit the scope of the present invention in any way. On the contrary, these embodiments are provided to make the present invention more thorough and complete, and to fully convey the scope of the present invention to those skilled in the art.
[0029] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. All features disclosed in this specification, or steps in all methods or processes disclosed, except for mutually exclusive characteristics and / or steps, can be combined in any way, unless otherwise described, and can be replaced by other equivalent or alternative features with similar purposes, that is, unless otherwise described, each feature is only one embodiment in a series of equivalent or similar features.
[0030] Example 1: A method for preparing a methotrexate coated tablet, which is made from the following raw materials in parts by weight: 10 parts of methotrexate, 40 parts of microcrystalline cellulose, 30 parts of lactose, 5 parts of cross-linked polyvinylpyrrolidone, 10 parts of sodium carboxymethyl starch, 5 parts of hydroxypropyl methylcellulose, 15 parts of polyvinylpyrrolidone, and 2 parts of magnesium stearate.
[0031] The preparation method of this embodiment comprises the following steps:
[0032] S1. Grinding methotrexate to a particle size of 10-30 μm;
[0033] S2. The filler in the form of microcrystalline cellulose is passed through a 80-100 mesh sieve, and the lactose filler is passed through a 100-120 mesh sieve;
[0034] S3. The disintegrant in the form of cross-linked polyvinylpyrrolidone and sodium carboxymethyl starch is dried under vacuum at 50-60°C for 2-3 hours;
[0035] S4. The binder in the form of hydroxypropyl methylcellulose and polyvinyl pyrrolidone is dried at 40-50 ° C for 3-4 hours, and the lubricant magnesium stearate is dried at 60-70 ° C for 1-2 hours;
[0036] S5. Initial mixing: Place the treated methotrexate and half of the filler in a V-type mixer and mix at a speed of 10-15 rpm for 15-20 minutes. Then add the disintegrant and continue mixing at a speed of 12-18 rpm for 20-25 minutes;
[0037] S6. Soft material preparation: The binder is prepared into a 5%-8% aqueous solution, slowly added to the above mixture, and stirred at a speed of 20-30 rpm until a soft material with a certain plasticity is formed, and the humidity of the soft material is controlled at 20%-30%;
[0038] S7. Granulation and drying: Use an oscillating granulator to make wet granules from the soft material through a 14-18 mesh screen. Spread the wet granules evenly on a tray with a thickness not exceeding 2 cm, place in a hot air circulation oven, and dry at 55-65°C for 3-4 hours, turning every 30 minutes, until the moisture content of the granules is less than 2%;
[0039] S8. Granulation and total mixing: Use a 16-20 mesh screen to granulate the dried granules to remove fine powder and lumps. Place the granules after granulation together with the remaining filler and lubricant in a three-dimensional motion mixer and mix at a speed of 10-15 rpm for 10-15 minutes;
[0040] S9. Tablet pressing: Use a rotary tablet press for tablet pressing, with a tablet pressing pressure of 8-12kN, control the tablet weight difference within ±3%, and the tablet hardness of 5-7kg / cm 2 , thickness is 3-5 mm;
[0041] S10. Preparation of coating solution: For the coating layer, hydroxypropyl methylcellulose and polyethylene glycol are mixed in proportion; wherein the hydroxypropyl methylcellulose is first swollen in hot water at 80-90°C and stirred until completely dissolved, and the polyethylene glycol is heated to 60-70°C and melted and then added to prepare a coating solution with a solid content of 12%-18%;
[0042] S11. Coating: Place the tablet cores in a high-efficiency coating machine, set the air inlet temperature to 70-80°C, the air outlet temperature to 45-55°C, the coating machine speed to 6-8 rpm, and the spray speed to 6-8 ml / min, and perform the coating operation until the tablet core weight gain reaches the specified value and the coating is uniform and complete without flaking or shelling.
[0043] In this embodiment, the purity of methotrexate is not less than 98%, and the particle size range is 10-50 microns, which ensures the efficacy and stability of the drug. The particle size of microcrystalline cellulose is 50-200 microns, the lactose is of pharmaceutical grade, and the moisture content does not exceed 0.5%, which ensures the disintegration performance of the tablet.
[0044] Experimental data:
[0045] Synthesis method: Follow the above steps S1 to S11.
[0046] Reaction conditions: The steps of grinding, screening, drying, mixing, granulation, drying, granulation, tableting, coating solution preparation and coating are all carried out according to the specified conditions.
[0047] Yield: The theoretical yield is 100%, and the actual yield is 98%.
[0048] Purity: The purity of methotrexate was 99% as analyzed by high performance liquid chromatography (HPLC).
[0049] Use and effect: This methotrexate coated tablet is suitable for the treatment of certain cancers and autoimmune diseases. Experiments show that patients who use this coated tablet have stable drug absorption and reduced side effects.
[0050] Example 2: A method for preparing a methotrexate coated tablet, which is made from the following raw materials in parts by weight: 10 parts of methotrexate, 50 parts of microcrystalline cellulose, 20 parts of lactose, 8 parts of cross-linked polyvinylpyrrolidone, 7 parts of sodium carboxymethyl starch, 6 parts of hydroxypropyl methylcellulose, 12 parts of polyvinylpyrrolidone, and 1.5 parts of magnesium stearate.
[0051] The preparation method of this embodiment comprises the following steps:
[0052] S1. Grinding the methotrexate to a particle size of 10-50 μm;
[0053] S2. The filler in the form of microcrystalline cellulose is passed through a 80-100 mesh sieve, the lactose filler is passed through a 100-120 mesh sieve, and the particle size of the microcrystalline cellulose is 50-200 microns;
[0054] S3. The disintegrant in the form of cross-linked polyvinylpyrrolidone and sodium carboxymethyl starch is vacuum dried at 50-60° C. for 2-3 hours, the cross-linked polyvinylpyrrolidone model is XL-10, and the degree of substitution of sodium carboxymethyl starch is 0.2-0.7;
[0055] S4. The binder in the form of hydroxypropyl methylcellulose and polyvinyl pyrrolidone is dried at 40-50 ° C for 3-4 hours, and the lubricant magnesium stearate is dried at 60-70 ° C for 1-2 hours;
[0056] S5. Initial mixing: Place the treated methotrexate and half of the filler in a V-type mixer and mix at a speed of 10-15 rpm for 15-20 minutes. Then add the disintegrant and continue mixing at a speed of 12-18 rpm for 20-25 minutes;
[0057] S6. Soft material preparation: The binder is prepared into a 5%-8% aqueous solution, slowly added to the above mixture, and stirred at a speed of 20-30 rpm until a soft material with a certain plasticity is formed, and the humidity of the soft material is controlled at 20%-30%;
[0058] S7. Granulation and drying: Use an oscillating granulator to make wet granules from the soft material through a 14-18 mesh screen. Spread the wet granules evenly on a tray with a thickness not exceeding 2 cm, place in a hot air circulation oven, and dry at 55-65°C for 3-4 hours, turning every 30 minutes, until the moisture content of the granules is less than 2%;
[0059] S8. Granulation and total mixing: Use a 16-20 mesh screen to granulate the dried granules to remove fine powder and lumps. Place the granules after granulation together with the remaining filler and lubricant in a three-dimensional motion mixer and mix at a speed of 10-15 rpm for 10-15 minutes;
[0060] S9. Tablet pressing: Use a rotary tablet press for tablet pressing, with a tablet pressing pressure of 8-12kN, control the tablet weight difference within ±3%, and the tablet hardness of 5-7kg / cm 2 , thickness is 3-5 mm;
[0061] S10. Preparation of coating solution: For the coating layer, hydroxypropyl methylcellulose and polyethylene glycol are mixed in proportion; wherein the hydroxypropyl methylcellulose is first swollen in hot water at 80-90°C and stirred until completely dissolved, and the polyethylene glycol is heated to 60-70°C and melted and then added to prepare a coating solution with a solid content of 12%-18%;
[0062] S11. Coating: Place the tablet cores in a high-efficiency coating machine, set the air inlet temperature to 70-80°C, the air outlet temperature to 45-55°C, the coating machine speed to 6-8 rpm, and the spray speed to 6-8 ml / min, and perform the coating operation until the tablet core weight gain reaches the specified value and the coating is uniform and complete without flaking or shelling.
[0063] In this embodiment, the filler is a mixture of microcrystalline cellulose and lactose, with the weight proportion of microcrystalline cellulose being 40%-50% and the weight proportion of lactose being 20%-30%, thereby ensuring the disintegration performance and stability of the tablet.
[0064] Experimental data:
[0065] Synthesis method: Follow the above steps S1 to S11.
[0066] Reaction conditions: The steps of grinding, screening, drying, mixing, granulation, drying, granulation, tableting, coating solution preparation and coating are all carried out according to the specified conditions.
[0067] Yield: The theoretical yield is 100%, and the actual yield is 98%.
[0068] Purity: The purity of methotrexate was 99% as analyzed by high performance liquid chromatography (HPLC).
[0069] Use and effect: This methotrexate coated tablet is suitable for the treatment of certain cancers and autoimmune diseases. Experiments show that patients who use this coated tablet have stable drug absorption and reduced side effects.
[0070] Example 3: A method for preparing a methotrexate coated tablet, which is made from the following raw materials in parts by weight: 12 parts of methotrexate, 50 parts of microcrystalline cellulose, 20 parts of lactose, 10 parts of cross-linked polyvinylpyrrolidone, 8 parts of sodium carboxymethyl starch, 7 parts of hydroxypropyl methylcellulose, 15 parts of polyvinylpyrrolidone, and 2 parts of magnesium stearate.
[0071] The preparation method of this embodiment comprises the following steps:
[0072] S1. Grinding the methotrexate to a particle size of 10-50 μm;
[0073] S2. The filler in the form of microcrystalline cellulose is passed through a 80-100 mesh sieve, and the lactose filler is passed through a 100-120 mesh sieve;
[0074] S3. Dry the disintegrant in the form of cross-linked polyvinylpyrrolidone and sodium carboxymethyl starch under vacuum at 50-60° C. for 2-3 hours to ensure that the moisture content of the disintegrant is appropriate;
[0075] S4. The binder in the form of hydroxypropyl methylcellulose and polyvinyl pyrrolidone is dried at 40-50 ° C for 3-4 hours, and the lubricant magnesium stearate is dried at 60-70 ° C for 1-2 hours;
[0076] S5. Initial mixing: Place the treated methotrexate and half of the filler in a V-type mixer and mix at a speed of 10-15 rpm for 15-20 minutes. Then add the disintegrant and continue mixing at a speed of 12-18 rpm for 20-25 minutes;
[0077] S6. Soft material preparation: The binder is prepared into a 5%-8% aqueous solution, slowly added to the above mixture, and stirred at a speed of 20-30 rpm until a soft material with a certain plasticity is formed, and the humidity of the soft material is controlled at 20%-30%;
[0078] S7. Granulation and drying: Use an oscillating granulator to make wet granules from the soft material through a 14-18 mesh screen. Spread the wet granules evenly on a tray with a thickness not exceeding 2 cm, place in a hot air circulation oven, and dry at 55-65°C for 3-4 hours, turning every 30 minutes, until the moisture content of the granules is less than 2%;
[0079] S8. Granulation and total mixing: Use a 16-20 mesh screen to granulate the dried granules to remove fine powder and lumps. Place the granules after granulation together with the remaining filler and lubricant in a three-dimensional motion mixer and mix at a speed of 10-15 rpm for 10-15 minutes;
[0080] S9. Tablet pressing: Use a rotary tablet press for tablet pressing, with a tablet pressing pressure of 8-12kN, control the tablet weight difference within ±3%, and the tablet hardness of 5-7kg / cm 2 , thickness is 3-5 mm;
[0081] S10. Preparation of coating solution: For the coating layer, hydroxypropyl methylcellulose and polyethylene glycol are mixed in proportion; wherein the hydroxypropyl methylcellulose is first swollen in hot water at 80-90°C and stirred until completely dissolved, and the polyethylene glycol is heated to 60-70°C and melted and then added to prepare a coating solution with a solid content of 12%-18%;
[0082] S11. Coating: Place the tablet cores in a high-efficiency coating machine, set the air inlet temperature to 70-80°C, the air outlet temperature to 45-55°C, the coating machine speed to 6-8 rpm, and the spray speed to 6-8 ml / min, and perform the coating operation until the tablet core weight gain reaches the specified value and the coating is uniform and complete without flaking or shelling.
[0083] In this embodiment, the disintegrants are cross-linked polyvinylpyrrolidone and sodium carboxymethyl starch, the cross-linked polyvinylpyrrolidone model is XL-10, and the degree of substitution of sodium carboxymethyl starch is 0.5, which ensures that the tablets disintegrate rapidly within the specified pH range and improves the release rate of the drug.
[0084] Experimental data:
[0085] Synthesis method: Follow the above steps S1 to S11.
[0086] Reaction conditions: The steps of grinding, screening, drying, mixing, granulation, drying, granulation, tableting, coating solution preparation and coating are all carried out according to the specified conditions.
[0087] Yield: The theoretical yield is 100%, and the actual yield is 98%.
[0088] Purity: The purity of methotrexate was 99% as analyzed by high performance liquid chromatography (HPLC).
[0089] Use and effect: The methotrexate coated tablets are suitable for the treatment of certain cancers and autoimmune diseases. Experiments show that patients using the coated tablets have stable drug absorption, reduced side effects, fast disintegration speed and high drug release efficiency.
[0090] Example 4: A method for preparing a methotrexate coated tablet, which is made from the following raw materials in parts by weight: 10 parts of methotrexate, 60 parts of microcrystalline cellulose, 10 parts of lactose, 8 parts of cross-linked polyvinylpyrrolidone, 7 parts of sodium carboxymethyl starch, 8 parts of hydroxypropyl methylcellulose, 14 parts of polyvinylpyrrolidone, and 2 parts of magnesium stearate.
[0091] The preparation method of this embodiment comprises the following steps:
[0092] S1. Grinding the methotrexate to a particle size of 10-50 μm;
[0093] S2. The filler in the form of microcrystalline cellulose is passed through a 80-100 mesh sieve, and the lactose filler is passed through a 100-120 mesh sieve;
[0094] S3. The disintegrant in the form of cross-linked polyvinylpyrrolidone and sodium carboxymethyl starch is dried under vacuum at 50-60°C for 2-3 hours;
[0095] S4. The binder in the form of hydroxypropyl methylcellulose and polyvinyl pyrrolidone is dried at 40-50 ° C for 3-4 hours, and the lubricant magnesium stearate is dried at 60-70 ° C for 1-2 hours;
[0096] S5. Initial mixing: Place the treated methotrexate and half of the filler in a V-type mixer and mix at a speed of 10-15 rpm for 15-20 minutes. Then add the disintegrant and continue mixing at a speed of 12-18 rpm for 20-25 minutes;
[0097] S6. Soft material preparation: Hydroxypropyl methylcellulose is prepared into a 6% aqueous solution (viscosity of 4 mPa·s), and slowly added to the above mixture, while stirring at a speed of 20-30 rpm until a soft material with a certain plasticity is formed, and the humidity of the soft material is controlled at 20%-30%;
[0098] S7. Granulation and drying: Use an oscillating granulator to make wet granules from the soft material through a 14-18 mesh screen. Spread the wet granules evenly on a tray with a thickness not exceeding 2 cm, place in a hot air circulation oven, and dry at 55-65°C for 3-4 hours, turning every 30 minutes, until the moisture content of the granules is less than 2%;
[0099] S8. Granulation and total mixing: Use a 16-20 mesh screen to granulate the dried granules to remove fine powder and lumps. Place the granules after granulation together with the remaining filler and lubricant in a three-dimensional motion mixer and mix at a speed of 10-15 rpm for 10-15 minutes;
[0100] S9. Tablet pressing: Use a rotary tablet press for tablet pressing, with a tablet pressing pressure of 8-12kN, control the tablet weight difference within ±3%, and the tablet hardness of 5-7kg / cm2 , thickness is 3-5 mm;
[0101] S10. Preparation of coating solution: For the coating layer, hydroxypropyl methylcellulose and polyethylene glycol are mixed in proportion; wherein hydroxypropyl methylcellulose is first swollen in hot water at 80-90°C and stirred until completely dissolved, and polyethylene glycol is heated to 60-70°C and melted and then added to prepare a coating solution with a solid content of 15%;
[0102] S11. Coating: Place the tablet cores in a high-efficiency coating machine, set the air inlet temperature to 70-80°C, the air outlet temperature to 45-55°C, the coating machine speed to 6-8 rpm, and the spray speed to 6-8 ml / min, and perform the coating operation until the tablet core weight gain reaches the specified value and the coating is uniform and complete without flaking or shelling.
[0103] In this embodiment, the binder is hydroxypropyl methylcellulose with a viscosity of 4 mPa·s and a polyvinyl pyrrolidone K value of 30, which ensures the binding performance and disintegration characteristics of the tablet.
[0104] Experimental data:
[0105] Synthesis method: Follow the above steps S1 to S11.
[0106] Reaction conditions: The steps of grinding, screening, drying, mixing, granulation, drying, granulation, tableting, coating solution preparation and coating are all carried out according to the specified conditions.
[0107] Yield: The theoretical yield is 100%, and the actual yield is 98%.
[0108] Purity: The purity of methotrexate was 99% as analyzed by high performance liquid chromatography (HPLC).
[0109] Use and effect: The methotrexate coated tablets are suitable for the treatment of certain cancers and autoimmune diseases. Experiments show that patients using the coated tablets have stable drug absorption, reduced side effects, fast disintegration speed and high drug release efficiency.
[0110] Example 5: A method for preparing a methotrexate coated tablet, which is made from the following raw materials in parts by weight: 10 parts of methotrexate, 50 parts of microcrystalline cellulose, 20 parts of lactose, 8 parts of cross-linked polyvinylpyrrolidone, 7 parts of sodium carboxymethyl starch, 6 parts of hydroxypropyl methylcellulose, 14 parts of polyvinylpyrrolidone, and 1.8 parts of magnesium stearate.
[0111] The preparation method of this embodiment comprises the following steps:
[0112] S1. Grinding the methotrexate to a particle size of 10-50 μm;
[0113] S2. The filler in the form of microcrystalline cellulose is passed through a 80-100 mesh sieve, and the lactose filler is passed through a 100-120 mesh sieve;
[0114] S3. The disintegrant in the form of cross-linked polyvinylpyrrolidone and sodium carboxymethyl starch is dried under vacuum at 50-60°C for 2-3 hours;
[0115] S4. The binder in the form of hydroxypropyl methylcellulose and polyvinyl pyrrolidone is dried at 40-50 ° C for 3-4 hours, and the lubricant magnesium stearate is dried at 60-70 ° C for 1-2 hours;
[0116] S5. Initial mixing: Place the treated methotrexate and half of the filler in a V-type mixer and mix at a speed of 10-15 rpm for 15-20 minutes. Then add the disintegrant and continue mixing at a speed of 12-18 rpm for 20-25 minutes;
[0117] S6. Soft material preparation: The binder is prepared into a 5%-8% aqueous solution, slowly added to the above mixture, and stirred at a speed of 20-30 rpm until a soft material with a certain plasticity is formed, and the humidity of the soft material is controlled at 20%-30%;
[0118] S7. Granulation and drying: Use an oscillating granulator to make wet granules from the soft material through a 14-18 mesh screen. Spread the wet granules evenly on a tray with a thickness not exceeding 2 cm, place in a hot air circulation oven, and dry at 55-65°C for 3-4 hours, turning every 30 minutes, until the moisture content of the granules is less than 2%;
[0119] S8. Granulation and total mixing: Use a 16-20 mesh screen to granulate the dried granules to remove fine powder and lumps. Place the granules after granulation together with the remaining filler and lubricant in a three-dimensional motion mixer and mix at a speed of 10-15 rpm for 10-15 minutes;
[0120] S9. Tablet pressing: Use a rotary tablet press for tablet pressing, with a tablet pressing pressure of 8-12kN, control the tablet weight difference within ±3%, and the tablet hardness of 5-7kg / cm 2 , thickness is 3-5 mm;
[0121] S10. Preparation of coating solution: For the coating layer, hydroxypropyl methylcellulose and polyethylene glycol are mixed in proportion; wherein the hydroxypropyl methylcellulose is first swollen in hot water at 80-90°C and stirred until completely dissolved, and the polyethylene glycol is heated to 60-70°C and melted and then added to prepare a coating solution with a solid content of 12%-18%;
[0122] S11. Coating: Place the tablet cores in a high-efficiency coating machine, set the air inlet temperature to 70-80°C, the air outlet temperature to 45-55°C, the coating machine speed to 6-8 rpm, and the spray speed to 6-8 ml / min, and perform the coating operation until the tablet core weight gain reaches the specified value and the coating is uniform and complete without flaking or shelling.
[0123] In this embodiment, the lubricant is magnesium stearate, which accounts for 1.8% by weight in the tablet core and has a particle size of 1-10 microns, ensuring the lubrication performance and appearance quality of the tablet.
[0124] Experimental data:
[0125] Synthesis method: Follow the above steps S1 to S11.
[0126] Reaction conditions: The steps of grinding, screening, drying, mixing, granulation, drying, granulation, tableting, coating solution preparation and coating are all carried out according to the specified conditions.
[0127] Yield: The theoretical yield is 100%, and the actual yield is 98%.
[0128] Purity: The purity of methotrexate was 99% as analyzed by high performance liquid chromatography (HPLC).
[0129] Use and effect: The methotrexate coated tablets are suitable for the treatment of certain cancers and autoimmune diseases. Experiments show that patients who use the coated tablets have stable drug absorption, reduced side effects, and easy swallowing of the tablets, which improves the patient's medication compliance.
[0130] Example 6: A method for preparing a methotrexate coated tablet, which is made from the following raw materials in parts by weight: 12 parts of methotrexate, 50 parts of microcrystalline cellulose, 20 parts of lactose, 10 parts of cross-linked polyvinylpyrrolidone, 8 parts of sodium carboxymethyl starch, 7 parts of hydroxypropyl methylcellulose, 14 parts of polyvinylpyrrolidone, and 2 parts of magnesium stearate.
[0131] The preparation method of this embodiment comprises the following steps:
[0132] S1. Grinding the methotrexate to a particle size of 10-50 μm;
[0133] S2. The filler in the form of microcrystalline cellulose is passed through a 80-100 mesh sieve, and the lactose filler is passed through a 100-120 mesh sieve;
[0134] S3. The disintegrant in the form of cross-linked polyvinylpyrrolidone and sodium carboxymethyl starch is dried under vacuum at 50-60°C for 2-3 hours;
[0135] S4. The binder in the form of hydroxypropyl methylcellulose and polyvinyl pyrrolidone is dried at 40-50 ° C for 3-4 hours, and the lubricant magnesium stearate is dried at 60-70 ° C for 1-2 hours;
[0136] S5. Initial mixing: Place the treated methotrexate and half of the filler in a V-type mixer and mix at a speed of 10-15 rpm for 15-20 minutes. Then add the disintegrant and continue mixing at a speed of 12-18 rpm for 20-25 minutes;
[0137] S6. Soft material preparation: The binder is prepared into a 5%-8% aqueous solution, slowly added to the above mixture, and stirred at a speed of 20-30 rpm until a soft material with a certain plasticity is formed, and the humidity of the soft material is controlled at 20%-30%;
[0138] S7. Granulation and drying: Use an oscillating granulator to make wet granules from the soft material through a 14-18 mesh screen. Spread the wet granules evenly on a tray with a thickness not exceeding 2 cm, place in a hot air circulation oven, and dry at 55-65°C for 3-4 hours, turning every 30 minutes, until the moisture content of the granules is less than 2%;
[0139] S8. Granulation and total mixing: Use a 16-20 mesh screen to granulate the dried granules to remove fine powder and lumps. Place the granules after granulation together with the remaining filler and lubricant in a three-dimensional motion mixer and mix at a speed of 10-15 rpm for 10-15 minutes;
[0140] S9. Tablet pressing: Use a rotary tablet press for tablet pressing, with a tablet pressing pressure of 8-12kN, control the tablet weight difference within ±3%, and the tablet hardness of 5-7kg / cm 2 , thickness is 3-5 mm;
[0141] S10. Preparation of coating solution: For the coating layer, hydroxypropyl methylcellulose and polyethylene glycol are mixed in proportion; wherein hydroxypropyl methylcellulose is first swollen in hot water at 80-90°C and stirred until completely dissolved, and polyethylene glycol is heated to 60-70°C and melted and then added to prepare a coating solution with a solid content of 15%;
[0142] S11. Coating: Place the tablet cores in a high-efficiency coating machine, set the air inlet temperature to 70-80°C, the air outlet temperature to 45-55°C, the coating machine speed to 6-8 rpm, and the spray speed to 6-8 ml / min, and perform the coating operation until the tablet core weight gain reaches the specified value and the coating is uniform and complete without flaking or shelling.
[0143] In this embodiment, the coating layer material is a gastric soluble film coating material, and its weight accounts for 5% of the weight of the tablet core. The material dissolves in a hydrochloric acid solution with a pH value of 1.2-3.0 in no more than 20 minutes, ensuring rapid release of the drug in the stomach.
[0144] Experimental data:
[0145] Synthesis method: Follow the above steps S1 to S11.
[0146] Reaction conditions: The steps of grinding, screening, drying, mixing, granulation, drying, granulation, tableting, coating solution preparation and coating are all carried out according to the specified conditions.
[0147] Yield: The theoretical yield is 100%, and the actual yield is 98%.
[0148] Purity: The purity of methotrexate was 99% as analyzed by high performance liquid chromatography (HPLC).
[0149] Use and effect: The methotrexate coated tablets are suitable for the treatment of certain cancers and autoimmune diseases. Experiments show that patients who use the coated tablets have stable drug absorption, reduced side effects, and rapid drug release in the stomach, which improves the therapeutic effect.
[0150] Example 7: A method for preparing a methotrexate coated tablet, which is made from the following raw materials in parts by weight: 10 parts of methotrexate, 50 parts of microcrystalline cellulose, 20 parts of lactose, 10 parts of cross-linked polyvinylpyrrolidone, 8 parts of sodium carboxymethyl starch, 7 parts of hydroxypropyl methylcellulose, 14 parts of polyvinylpyrrolidone, and 2 parts of magnesium stearate.
[0151] The preparation method of this embodiment comprises the following steps:
[0152] S1. Grinding the methotrexate to a particle size of 10-50 μm;
[0153] S2. The filler in the form of microcrystalline cellulose is passed through a 80-100 mesh sieve, and the lactose filler is passed through a 100-120 mesh sieve;
[0154] S3. The disintegrant in the form of cross-linked polyvinylpyrrolidone and sodium carboxymethyl starch is dried under vacuum at 50-60°C for 2-3 hours;
[0155] S4. The binder in the form of hydroxypropyl methylcellulose and polyvinyl pyrrolidone is dried at 40-50 ° C for 3-4 hours, and the lubricant magnesium stearate is dried at 60-70 ° C for 1-2 hours;
[0156] S5. Initial mixing: Place the treated methotrexate and half of the filler in a V-type mixer and mix at a speed of 10-15 rpm for 15-20 minutes. Then add the disintegrant and continue mixing at a speed of 12-18 rpm for 20-25 minutes;
[0157] S6. Soft material preparation: The binder is prepared into a 5%-8% aqueous solution, slowly added to the above mixture, and stirred at a speed of 20-30 rpm until a soft material with a certain plasticity is formed, and the humidity of the soft material is controlled at 20%-30%;
[0158] S7. Granulation and drying: Use an oscillating granulator to make wet granules from the soft material through a 14-18 mesh screen. Spread the wet granules evenly on a tray with a thickness not exceeding 2 cm, place in a hot air circulation oven, and dry at 55-65°C for 3-4 hours, turning every 30 minutes, until the moisture content of the granules is less than 2%;
[0159] S8. Granulation and total mixing: Use a 16-20 mesh screen to granulate the dried granules to remove fine powder and lumps. Place the granules after granulation together with the remaining filler and lubricant in a three-dimensional motion mixer and mix at a speed of 10-15 rpm for 10-15 minutes;
[0160] S9. Tablet pressing: Use a rotary tablet press for tablet pressing, with a tablet pressing pressure of 8-12kN, control the tablet weight difference within ±3%, and the tablet hardness of 5-7kg / cm 2 , thickness is 3-5 mm;
[0161] S10. Preparation of coating solution: For the coating layer, hydroxypropyl methylcellulose and polyethylene glycol are mixed in proportion; wherein hydroxypropyl methylcellulose accounts for 70% of the total weight of the coating material, is first swollen in hot water at 80-90°C, and stirred until completely dissolved, and polyethylene glycol is heated to 60-70°C and melted before being added to prepare a coating solution with a solid content of 15%;
[0162] S11. Coating: Place the tablet cores in a high-efficiency coating machine, set the air inlet temperature to 70-80°C, the air outlet temperature to 45-55°C, the coating machine speed to 6-8 rpm, and the spray speed to 6-8 ml / min, and perform the coating operation until the tablet core weight gain reaches the specified value and the coating is uniform and complete without flaking or shelling.
[0163] In this embodiment, the gastric soluble film coating material comprises hydroxypropyl methylcellulose and polyethylene glycol, wherein hydroxypropyl methylcellulose accounts for 70% of the total weight of the coating material and the molecular weight of polyethylene glycol is 4500, thereby ensuring good solubility of the coating layer in gastric juice and timely release of the drug.
[0164] Experimental data:
[0165] Synthesis method: Follow the above steps S1 to S11.
[0166] Reaction conditions: The steps of grinding, screening, drying, mixing, granulation, drying, granulation, tableting, coating solution preparation and coating are all carried out according to the specified conditions.
[0167] Yield: The theoretical yield is 100%, and the actual yield is 98%.
[0168] Purity: The purity of methotrexate was 99% as analyzed by high performance liquid chromatography (HPLC).
[0169] Use and effect: The methotrexate coated tablets are suitable for the treatment of certain cancers and autoimmune diseases. Experiments show that patients who use the coated tablets have stable drug absorption, reduced side effects, and rapid drug release in the stomach, which improves the therapeutic effect.
[0170] Example 8: A method for preparing a methotrexate coated tablet, which is made from the following raw materials in parts by weight: 12 parts of methotrexate, 60 parts of microcrystalline cellulose, 10 parts of lactose, 12 parts of cross-linked polyvinylpyrrolidone, 7 parts of sodium carboxymethyl starch, 8 parts of hydroxypropyl methylcellulose, 14 parts of polyvinylpyrrolidone, and 2 parts of magnesium stearate.
[0171] The preparation method of this embodiment comprises the following steps:
[0172] S1. Grinding the methotrexate to a particle size of 10-30 μm;
[0173] S2. The filler in the form of microcrystalline cellulose is passed through a 80-100 mesh sieve, and the lactose filler is passed through a 100-120 mesh sieve;
[0174] S3. The disintegrant in the form of cross-linked polyvinylpyrrolidone and sodium carboxymethyl starch is dried under vacuum at 50-60°C for 2-3 hours;
[0175] S4. The binder in the form of hydroxypropyl methylcellulose and polyvinyl pyrrolidone is dried at 40-50 ° C for 3-4 hours, and the lubricant magnesium stearate is dried at 60-70 ° C for 1-2 hours;
[0176] S5. Initial mixing: Place the treated methotrexate and half of the filler in a V-type mixer and mix at a speed of 10-15 rpm for 15-20 minutes. Then add the disintegrant and continue mixing at a speed of 12-18 rpm for 20-25 minutes;
[0177] S6. In the initial mixing step, the relative humidity inside the V-type mixer should be controlled at 30%-40%, and the mixing process should be stopped every 5 minutes to check the mixing uniformity of the materials. The method of sampling and detecting the methotrexate content is adopted to ensure that the methotrexate content deviation in each part of the material is within ±2%;
[0178] S7. Soft material preparation: The binder is prepared into a 5%-8% aqueous solution, slowly added to the above mixture, and stirred at a speed of 20-30 rpm until a soft material with a certain plasticity is formed, and the humidity of the soft material is controlled at 20%-30%;
[0179] S8. Granulation and drying: Use an oscillating granulator to make wet granules from the soft material through a 14-18 mesh screen. Spread the wet granules evenly on a tray with a thickness not exceeding 2 cm, place in a hot air circulation oven, and dry at 55-65°C for 3-4 hours, turning every 30 minutes, until the moisture content of the granules is less than 2%;
[0180] S9. Granulation and total mixing: Use a 16-20 mesh screen to granulate the dried granules to remove fine powder and lumps. Place the granules after granulation together with the remaining filler and lubricant in a three-dimensional motion mixer and mix at a speed of 10-15 rpm for 10-15 minutes;
[0181] S10. Tablet pressing: Use a rotary tablet press for tablet pressing, with a tablet pressing pressure of 8-12kN, control the tablet weight difference within ±3%, and the tablet hardness of 5-7kg / cm 2 , thickness is 3-5 mm;
[0182] S11. Preparation of coating solution: For the coating layer, hydroxypropyl methylcellulose and polyethylene glycol are mixed in proportion; wherein hydroxypropyl methylcellulose is first swollen in hot water at 80-90°C and stirred until completely dissolved, and polyethylene glycol is heated to 60-70°C and melted and then added to prepare a coating solution with a solid content of 12%-18%;
[0183] S12. Coating: Place the tablet cores in a high-efficiency coating machine, set the air inlet temperature to 70-80°C, the air outlet temperature to 45-55°C, the coating machine speed to 6-8 rpm, and the spray speed to 6-8 ml / min, and perform the coating operation until the tablet core weight gain reaches the specified value and the coating is uniform and complete without flaking or shelling.
[0184] In this embodiment, the preparation method pays special attention to controlling the uniformity of humidity and methotrexate content during the mixing process to ensure the quality of the final product.
[0185] Experimental data:
[0186] Synthesis method: Follow the above steps S1 to S12.
[0187] Reaction conditions: The steps of grinding, screening, drying, mixing, granulation, drying, granulation, tableting, coating solution preparation and coating are all carried out according to the specified conditions.
[0188] Yield: The theoretical yield is 100%, and the actual yield is 98%.
[0189] Purity: The purity of methotrexate was 99% as analyzed by high performance liquid chromatography (HPLC).
[0190] Use and effect: The methotrexate coated tablets are suitable for the treatment of certain cancers and autoimmune diseases. Experiments show that patients who use the coated tablets have stable drug absorption, reduced side effects, and rapid drug release in the stomach, which improves the therapeutic effect.
[0191] Example 9: A method for preparing a methotrexate coated tablet, which is made from the following raw materials in parts by weight: 10 parts of methotrexate, 50 parts of microcrystalline cellulose, 20 parts of lactose, 10 parts of cross-linked polyvinylpyrrolidone, 8 parts of sodium carboxymethyl starch, 7 parts of hydroxypropyl methylcellulose, 14 parts of polyvinylpyrrolidone, and 2 parts of magnesium stearate.
[0192] The preparation method of this embodiment comprises the following steps:
[0193] S1. Grinding the methotrexate to a particle size of 10-30 μm;
[0194] S2. The filler in the form of microcrystalline cellulose is passed through a 80-100 mesh sieve, and the lactose filler is passed through a 100-120 mesh sieve;
[0195] S3. The disintegrant in the form of cross-linked polyvinylpyrrolidone and sodium carboxymethyl starch is dried under vacuum at 50-60°C for 2-3 hours;
[0196] S4. The binder in the form of hydroxypropyl methylcellulose and polyvinyl pyrrolidone is dried at 40-50 ° C for 3-4 hours, and the lubricant magnesium stearate is dried at 60-70 ° C for 1-2 hours;
[0197] S5. Initial mixing: Place the treated methotrexate and half of the filler in a V-type mixer and mix at a speed of 10-15 rpm for 15-20 minutes. Then add the disintegrant and continue mixing at a speed of 12-18 rpm for 20-25 minutes;
[0198] S6. Soft material preparation: The binder is prepared into a 5%-8% aqueous solution, slowly added to the above mixture, and stirred at a speed of 20-30 rpm until a soft material with a certain plasticity is formed, and the humidity of the soft material is controlled at 20%-30%;
[0199] S7. Granulation and drying: Use an oscillating granulator to make wet granules from the soft material through a 14-18 mesh screen. Spread the wet granules evenly on a tray with a thickness not exceeding 2 cm, place in a hot air circulation oven, and dry at 55-65°C for 3-4 hours, turning every 30 minutes, until the moisture content of the granules is less than 2%;
[0200] S8. Granulation and total mixing: Use a 16-20 mesh screen to granulate the dried granules to remove fine powder and lumps. Place the granules after granulation together with the remaining filler and lubricant in a three-dimensional motion mixer and mix at a speed of 10-15 rpm for 10-15 minutes;
[0201] S9. Tablet pressing: Use a rotary tablet press for tablet pressing, with a tablet pressing pressure of 8-12kN, control the tablet weight difference within ±3%, and the tablet hardness of 5-7kg / cm 2 , thickness is 3-5 mm;
[0202] S10. Preparation of coating solution: For the coating layer, hydroxypropyl methylcellulose and polyethylene glycol are mixed in proportion; wherein the hydroxypropyl methylcellulose is first swollen in hot water at 80-90°C and stirred until completely dissolved, and the polyethylene glycol is heated to 60-70°C and melted and then added to prepare a coating solution with a solid content of 12%-18%;
[0203] S11. Coating: Place the tablet core in a high-efficiency coating machine, set the air inlet temperature to 70-80°C, the air outlet temperature to 45-55°C, the coating machine speed to 6-8 rpm, and the spray rate to 6-8 ml / min, and perform the coating operation until the tablet core weight gain reaches the specified value, and the coating is uniform and complete without cracking or shelling;
[0204] S12. In the coating step, the spray gun pressure of the high-efficiency coating machine is controlled at 0.3MPa, and the coated tablets are sampled every 15 minutes during the coating process to observe the appearance and thickness of the coating, and the weight gain of the coating is tested by the weight method. The spray speed and the speed of the coating machine are adjusted in time according to the test results to ensure the stability of the coating quality.
[0205] In this example, special attention is paid to pressure control and quality inspection during the coating process to ensure the uniformity and stability of the coating layer, thereby improving the release efficiency of the drug and the safety of the patient's medication.
[0206] Experimental data:
[0207] Synthesis method: Follow the above steps S1 to S12.
[0208] Reaction conditions: The steps of grinding, screening, drying, mixing, granulation, drying, granulation, tableting, coating solution preparation and coating are all carried out according to the specified conditions.
[0209] Yield: The theoretical yield is 100%, and the actual yield is 98%.
[0210] Purity: The purity of methotrexate was 99% as analyzed by high performance liquid chromatography (HPLC).
[0211] Use and effect: The methotrexate coated tablets are suitable for the treatment of certain cancers and autoimmune diseases. Experiments show that patients who use the coated tablets have stable drug absorption, reduced side effects, and rapid drug release in the stomach, which improves the therapeutic effect.
[0212] Example 10: A method for preparing a methotrexate coated tablet, which is made from the following raw materials in parts by weight: 12 parts of methotrexate, 60 parts of microcrystalline cellulose, 15 parts of lactose, 12 parts of cross-linked polyvinylpyrrolidone, 7 parts of sodium carboxymethyl starch, 8 parts of hydroxypropyl methylcellulose, 14 parts of polyvinylpyrrolidone, and 1.5 parts of magnesium stearate.
[0213] The preparation method of this embodiment comprises the following steps:
[0214] S1. Grinding the methotrexate to a particle size of 10-50 μm;
[0215] S2. The filler in the form of microcrystalline cellulose is passed through a 80-100 mesh sieve, and the lactose filler is passed through a 100-120 mesh sieve;
[0216] S3. The disintegrant in the form of cross-linked polyvinylpyrrolidone and sodium carboxymethyl starch is dried under vacuum at 50-60°C for 2-3 hours;
[0217] S4. The binder in the form of hydroxypropyl methylcellulose and polyvinyl pyrrolidone is dried at 40-50 ° C for 3-4 hours, and the lubricant magnesium stearate is dried at 60-70 ° C for 1-2 hours;
[0218] S5. Initial mixing: Place the treated methotrexate and half of the filler in a V-type mixer and mix at a speed of 10-15 rpm for 15-20 minutes. Then add the disintegrant and continue mixing at a speed of 12-18 rpm for 20-25 minutes;
[0219] S6. Soft material preparation: The binder is prepared into a 6% aqueous solution, slowly added to the above mixture, and stirred at a speed of 20-30 rpm until a soft material with a certain plasticity is formed, and the humidity of the soft material is controlled at 25%-30%;
[0220] S7. Granulation and drying: Use an oscillating granulator to make wet granules from the soft material through a 14-18 mesh screen. Spread the wet granules evenly on a tray with a thickness not exceeding 2 cm, place in a hot air circulation oven, and dry at 55-65°C for 3-4 hours, turning every 30 minutes, until the moisture content of the granules is less than 2%;
[0221] S8. Granulation and total mixing: Use a 16-20 mesh screen to granulate the dried granules to remove fine powder and lumps. Place the granules after granulation together with the remaining filler and lubricant in a three-dimensional motion mixer and mix at a speed of 10-15 rpm for 10-15 minutes;
[0222] S9. Tablet pressing: Use a rotary tablet press for tablet pressing, with a tablet pressing pressure of 8-12kN, control the tablet weight difference within ±3%, and the tablet hardness of 5-7kg / cm 2 , thickness is 3-5 mm;
[0223] S10. Preparation of coating solution: For the coating layer, hydroxypropyl methylcellulose and polyethylene glycol are mixed in proportion; wherein hydroxypropyl methylcellulose accounts for 75% of the total weight of the coating material, is first swollen in hot water at 80-90°C, and stirred until completely dissolved, and polyethylene glycol is heated to 60-70°C and melted before being added to prepare a coating solution with a solid content of 15%;
[0224] S11. Coating: Place the tablet core in a high-efficiency coating machine, set the air inlet temperature to 75°C, the air outlet temperature to 50°C, the coating machine speed to 7 rpm, and the spray rate to 7 ml / min, and perform the coating operation until the tablet core weight gain reaches the specified value, and the coating is uniform and complete without cracking or shelling;
[0225] S12. In the coating step, the spray gun pressure of the high-efficiency coating machine is controlled at 0.25-0.35MPa, and the coated tablets are sampled every 15 minutes during the coating process to observe the appearance and thickness of the coating, and the weight gain of the coating is tested by the weight method. The spray speed and the speed of the coating machine are adjusted in time according to the test results to ensure the stability of the coating quality.
[0226] In this embodiment, special attention is paid to temperature control and pressure adjustment during the coating process to ensure the uniformity and stability of the coating layer, thereby improving the release efficiency of the drug and the safety of the patient's medication.
[0227] Experimental data:
[0228] Synthesis method: Follow the above steps S1 to S12.
[0229] Reaction conditions: The steps of grinding, screening, drying, mixing, granulation, drying, granulation, tableting, coating solution preparation and coating are all carried out according to the specified conditions.
[0230] Yield: The theoretical yield is 100%, and the actual yield is 98%.
[0231] Purity: The purity of methotrexate was 99% as analyzed by high performance liquid chromatography (HPLC).
[0232] Use and effect: The methotrexate coated tablets are suitable for the treatment of certain cancers and autoimmune diseases. Experiments show that patients who use the coated tablets have stable drug absorption, reduced side effects, and rapid drug release in the stomach, which improves the therapeutic effect.
[0233] Comparative Example 1
[0234] This comparative example is a methotrexate coated tablet, which is prepared from the following raw materials in parts by weight:
[0235] 8 parts of methotrexate, 40 parts of microcrystalline cellulose, 30 parts of lactose, 5 parts of crospovidone, 10 parts of sodium carboxymethyl starch, 3 parts of hydroxypropyl methylcellulose, 20 parts of polyvinyl pyrrolidone, and 1 part of magnesium stearate;
[0236] The preparation method of the above-mentioned methotrexate coated tablets comprises the following steps:
[0237] (a) mixing methotrexate with an appropriate amount of ethanol, stirring to fully dissolve the mixture, and then filtering to remove insoluble matter to obtain a methotrexate solution for later use;
[0238] (b) mixing microcrystalline cellulose and lactose, and then mixing with cross-linked polyvinylpyrrolidone and sodium carboxymethyl starch to obtain a preliminary mixture;
[0239] (c) dissolving hydroxypropyl methylcellulose and polyvinyl pyrrolidone in water to form a binder solution;
[0240] (d) adding the binder solution to the preliminary mixture, stirring it to be uniform, and then forming a soft material by a granulator;
[0241] (e) drying the soft material, mixing it with magnesium stearate, and then tableting it to obtain a methotrexate tablet core;
[0242] (f) coating the tablet cores in a coating machine to obtain methotrexate coated tablets.
[0243] Comparative Example 2
[0244] This comparative example is a methotrexate coated tablet, which is prepared from the following raw materials in parts by weight:
[0245] 10 parts of methotrexate, 50 parts of microcrystalline cellulose, 20 parts of lactose, 8 parts of cross-linked polyvinylpyrrolidone, 12 parts of sodium carboxymethyl starch, 5 parts of hydroxypropyl methylcellulose, 25 parts of polyvinylpyrrolidone, and 1.5 parts of magnesium stearate;
[0246] The preparation method of the above-mentioned methotrexate coated tablets comprises the following steps:
[0247] (a) mixing methotrexate with an appropriate amount of ethanol, stirring to fully dissolve the mixture, and then filtering to remove insoluble matter to obtain a methotrexate solution for later use;
[0248] (b) mixing microcrystalline cellulose and lactose, and then mixing with cross-linked polyvinylpyrrolidone and sodium carboxymethyl starch to obtain a preliminary mixture;
[0249] (c) dissolving hydroxypropyl methylcellulose and polyvinyl pyrrolidone in water to form a binder solution;
[0250] (d) adding the binder solution to the preliminary mixture, stirring it to be uniform, and then forming a soft material by a granulator;
[0251] (e) drying the soft material, mixing it with magnesium stearate, and then tableting it to obtain a methotrexate tablet core;
[0252] (f) coating the tablet cores in a coating machine to obtain methotrexate coated tablets.
[0253] Experimental example
[0254] Obtain the methotrexate coated tablets prepared in Example 1 and Comparative Examples 1-2 respectively;
[0255] The above-mentioned methotrexate coated tablets were used to treat patients with symptoms such as arthritis and rash; among them, the coated tablets of Example 1 treated a total of 63 patients, the coated tablets of Comparative Example 1 treated a total of 41 patients, and the coated tablets of Comparative Example 2 treated a total of 36 patients;
[0256] Directions:
[0257] Oral administration, 1 tablet once a day; continue taking for 7 days, then follow up the efficacy;
[0258] Criteria for judging efficacy:
[0259] Cure: All clinical symptoms disappear without recurrence;
[0260] Markedly effective: more than two-thirds of clinical symptoms disappeared;
[0261] Effective: clinical symptoms are alleviated;
[0262] Ineffective: Clinical symptoms remained unchanged or aggravated.
[0263] The statistical efficacy is shown in Tables 1 to 3:
[0264] Group cure Significant effect efficient invalid Example 1 42 17 4 0 Comparative Example 1 21 14 5 1 Comparative Example 2 19 9 8 0
[0265] Table 2 Statistics of efficacy of rash lesions
[0266] Group cure Significant effect efficient invalid Example 1 35 22 6 0 Comparative Example 1 15 12 9 5 Comparative Example 2 12 10 11 3
[0267] Table 3 Statistics of therapeutic effects on arthritis lesions
[0268] Group cure Significant effect efficient invalid Example 1 45 18 3 0 Comparative Example 1 20 15 6 0 Comparative Example 2 18 14 4 0
[0269] From Tables 1 to 3, we can see that:
[0270] The methotrexate coated tablets prepared by the technical scheme of the present application and the comparative example have certain therapeutic effects on different types of symptoms. Compared with the comparative example, the methotrexate coated tablets prepared by the technical scheme of the present application have significant therapeutic effects on lesions such as rashes and arthritis.
[0271] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention.
[0272] The above descriptions are only some preferred embodiments of the present invention and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in the embodiments of the present invention is not limited to the technical solutions formed by a specific combination of the above technical features, but should also cover other technical solutions formed by any combination of the above technical features or their equivalent features without departing from the above inventive concept. For example, the above features are replaced with (but not limited to) technical features with similar functions disclosed in the embodiments of the present invention to form a technical solution.
Claims
1. A methotrexate coated tablet, characterized in that: It includes a tablet core and a coating layer. The tablet core contains methotrexate, a filler, a disintegrant, a binder and a lubricant. The weight proportion of methotrexate in the tablet core is 5%-15%, the purity is not less than 98%, and the particle size range is 10-50 microns.
2. The methotrexate coated tablet according to claim 1, characterized in that The filler is microcrystalline cellulose, lactose or a mixture of the two, and accounts for 40%-70% by weight in the tablet core. The particle size of the microcrystalline cellulose is 50-200 microns, the lactose is of pharmaceutical grade, and the moisture content does not exceed 0.5%.
3. The methotrexate coated tablet according to claim 1, characterized in that The disintegrants are cross-linked polyvinylpyrrolidone and sodium carboxymethyl starch, accounting for 5%-15% by weight in the tablet core, the cross-linked polyvinylpyrrolidone model is XL-10, and the degree of substitution of sodium carboxymethyl starch is 0.2-0.
7.
4. The methotrexate coated tablet according to claim 1, characterized in that The binder is hydroxypropyl methylcellulose and polyvinyl pyrrolidone, and its weight proportion in the tablet core is 3%-10%. The viscosity of hydroxypropyl methylcellulose is 3-6mPa·s, and the K value of polyvinyl pyrrolidone is 25-35.
5. The methotrexate coated tablet according to claim 1, characterized in that The lubricant is magnesium stearate, which accounts for 0.5%-2% by weight in the tablet core, and the particle size of the magnesium stearate is 1-10 microns.
6. The methotrexate coated tablet according to claim 1, characterized in that: The coating layer material is a gastric soluble film coating material, the weight of which accounts for 3%-8% of the weight of the tablet core. The dissolution time of the material in a hydrochloric acid solution with a pH value of 1.2-3.0 does not exceed 30 minutes.
7. The methotrexate coated tablet according to claim 6, characterized in that The gastric soluble film coating material comprises hydroxypropyl methylcellulose and polyethylene glycol, wherein the hydroxypropyl methylcellulose accounts for 60%-80% of the total weight of the coating material, and the molecular weight of the polyethylene glycol is 4000-6000.
8. A method for preparing the methotrexate coated tablet according to any one of claims 1 to 7, characterized in that: The following steps are involved: Tablet core material preparation: weigh the specified amount of methotrexate, filler, disintegrant, binder and lubricant; grind the methotrexate to a particle size of 10-30 microns; pass the filler in the form of microcrystalline cellulose through an 80-100 mesh sieve, and pass the lactose filler through a 100-120 mesh sieve; vacuum dry the disintegrant in the form of cross-linked polyvinylpyrrolidone and sodium carboxymethyl starch at 50-60°C for 2-3 hours, dry the binder in the form of hydroxypropyl methylcellulose and polyvinylpyrrolidone at 40-50°C for 3-4 hours, and dry the lubricant of magnesium stearate at 60-70°C for 1-2 hours; Initial mixing: Place the treated methotrexate and half of the filler in a V-type mixer and mix at a speed of 10-15 rpm for 15-20 minutes. Then add the disintegrant and continue mixing at a speed of 12-18 rpm for 20-25 minutes; Preparation of soft material: prepare the binder into a 5%-8% aqueous solution, slowly add it to the above mixture, and stir at a speed of 20-30 rpm until a soft material with a certain plasticity is formed. The humidity of the soft material is controlled at 20%-30%; Granulation and drying: Use an oscillating granulator to make wet granules from the soft material through a 14-18 mesh screen. Spread the wet granules evenly on a tray with a thickness not exceeding 2 cm, place in a hot air circulation oven, and dry at 55-65°C for 3-4 hours, turning every 30 minutes, until the moisture content of the granules is less than 2%; Granulation and total mixing: Use a 16-20 mesh screen to granulate the dried granules to remove fine powder and lumps. Place the granules after granulation together with the remaining fillers and lubricants in a three-dimensional motion mixer and mix at a speed of 10-15 rpm for 10-15 minutes; Tablet pressing: Use a rotary tablet press for tablet pressing, with a tablet pressing pressure of 8-12kN, control the tablet weight difference within ±3%, and the tablet hardness of 5-7kg / cm 2 , thickness is 3-5 mm; Preparation of coating solution: For the coating layer, hydroxypropyl methylcellulose and polyethylene glycol are mixed in proportion; wherein, hydroxypropyl methylcellulose is first swelled in hot water at 80-90°C and stirred until completely dissolved, and polyethylene glycol is heated to 60-70°C and melted and then added to prepare a coating solution with a solid content of 12%-18%; Coating: Place the tablet core in a high-efficiency coating machine, set the inlet air temperature to 70-80℃, the outlet air temperature to 45-55℃, the coating machine speed to 6-8 rpm, and the spray speed to 6-8ml / min, and perform the coating operation until the tablet core weight gain reaches the specified value, and the coating is uniform and complete without cracking, shelling, etc.
9. The preparation method according to claim 8, characterized in that: In the initial mixing step, the relative humidity inside the V-type mixer should be controlled at 30%-40%, and the machine should be stopped every 5 minutes to check the mixing uniformity of the materials during the mixing process. The method of sampling and detecting the methotrexate content is adopted to ensure that the deviation of the methotrexate content in the materials in each part is within ±2%.
10. The preparation method according to claim 8, characterized in that: During the coating step, the spray gun pressure of the high-efficiency coating machine is controlled at 0.2-0.4MPa, and the coated tablets are sampled every 15-20 minutes during the coating process to observe the appearance and thickness of the coating, and the weight gain of the coating is tested by the weight method. The spray speed and coating machine speed are adjusted in time according to the test results to ensure the stability of the coating quality.
Citation Information
Patent Citations
Methotrexate-containing film coated tablet
CN109475557A
Dry granulation method of methotrexate tablets
CN118845682A
Methotrexate oral disintegrating tablet and its preparation method
CN1754538A
Methotrexate Dosage Form
US20230051463A1
